Discrete-time sliding mode control for uncertain networked system subject to time delay - Garcia, Saulo C. [UNESP]; Teixeira, Marcelo C. M. [UNESP]; Garcia, Jose Paulo F. [UNESP]; Alves, Uiliam N. L. T. [UNESP]; Ribeiro, Jean M. S. [UNESP] (Hindawi Publishing Corporation, 2015)
We deal with uncertain systems with networked sliding mode control, subject to time delay. To minimize the degenerative effects of the time delay, a simpler format of state predictor is proposed in the control law. Some ultimate bounded stability analyses and stabilization conditions are provided for the uncertain time delay system with proposed discrete-time sliding mode control strategy. A numerical example is presented to corroborate the analyses.